Corrigendum: Analytic representation theory of Lie groups: general theory and analytic globalizations of Harish-Chandra modules. (19th January 2017) - Gimperlein, Heiko; Krötz, Bernhard; Schlichtkrull, Henrik
Abstract : We correct the proof of the main result of the paper, Theorem 5.7. Our corrected proof relies on weaker versions of a number of intermediate results from the paper. The original, more general, versions of these statements are not known to be true.